[Aerial of Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of Heimaey from above. The town of white buildings with green and red roofs sit in a cluster to the left of black hills to the right. Grey oceans are visible in the background between mountainous, grass-covered mountains. White fumes sit along the black hills in the foreground.